Modified difficult-to-cure ceramic powder based on metal organic framework coating as well as preparation method and application of modified difficult-to-cure ceramic powder
By covering the metal organic frame material on the surface of difficult-to-cure ceramic powder, the problem of low photocuring depth of ceramic powder is solved, and high-efficiency photocuring and forming of ceramics is achieved.
Patent Information
- Application Number
- CN202411950953.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The difficult-to-cure ceramic powder has high UV absorbance, resulting in a low photocuring depth and is not easy to photocure.
By covering the metal organic frame material on the surface of the ceramic powder, the ultraviolet absorbance of the ceramic powder is reduced and the photocuring depth is improved.
It significantly reduces the ultraviolet absorbance of the difficult-to-cure ceramic powder, improves the photocuring depth, improves the curing performance of the ceramic slurry, and realizes photocuring forming.
Smart Images

Figure CN119751086A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing photocuring forming, and specifically relates to a metal organic framework-coated modified difficult-to-curing ceramic powder and a preparation method and application thereof. Background Art
[0002] Ceramic materials are inorganic non-metallic compounds prepared by liquid phase reaction and solid phase sintering of natural or synthetic compounds, and have many unique properties. Ceramics are widely used in defense, aerospace, machinery, electronics, biomedicine and other fields. With the gradual improvement of production and application requirements, the requirements for the shape and performance of ceramic parts are also getting higher and higher. Additive manufacturing technology is an advanced manufacturing technology that manufactures ceramic parts by stacking materials layer by layer. Compared with traditional ceramic processing methods, it does not require molds and has high material utilization rate. It has higher degrees of freedom and plasticity and can manufacture ceramics with complex shapes. Among them, photocuring forming technology has the characteristics of fast forming speed, high forming accuracy and low material loss. The use of photocuring forming technology to form ceramics with complex structures has broad prospects.
[0003] There are many studies on the preparation of ceramics by photocuring technology, such as aluminum oxide, zirconium oxide, silicon oxide, etc. The UV absorbance and refractive index of difficult-to-cured ceramic powders (silicon nitride, silicon carbide, PZT, etc.) are relatively high, resulting in a low curing depth of the ceramic slurry and difficulty in photocuring (J. Asian Ceram. Soc., 2022, 10 (1), 69-82.; J. Eur. Ceram. Soc., 2021, 41 (4), 2386-2394.). Studies have found that by reducing the absorbance of ceramic powders and reducing the refractive index difference between the powder and the photosensitive resin, the curing depth of the ceramic slurry can be increased, the curing performance of the ceramic slurry can be improved, and photocuring can be facilitated. Research has found that surface oxidation can significantly reduce the UV absorbance of difficult-to-cured ceramic powders and increase the curing depth, but the introduction of low-strength oxides will lead to reduced mechanical properties of non-oxide ceramics; sintering aid-coated modified difficult-to-cured ceramic powders can improve the curing properties of ceramic slurry, but this method is complex and requires high-temperature pretreatment, which increases the complexity and cost of the ceramic manufacturing process. Therefore, choosing a suitable method to reduce the UV absorbance of difficult-to-cured ceramic powders, reduce the refractive index difference between them and photosensitive resins, increase the curing depth, and prepare ceramic slurry that meets the conditions of photocuring forming is a key scientific problem to be solved in the preparation of difficult-to-cured ceramics using photocuring forming technology. Summary of the invention
[0004] In view of the defects of the prior art, the present invention provides a metal organic framework-coated modified difficult-to-curing ceramic powder and its preparation method and application, which aims to solve the technical problems of low photocuring depth and difficult photocuring forming of difficult-to-curing ceramic powder in the prior art.
[0005] According to a first aspect of the present invention, a method for preparing a modified ceramic powder coated with a metal organic framework is provided, comprising the following steps:
[0006] (1) adding a metal salt and an organic ligand into a solvent, mixing them thoroughly, and then adding them into a reaction vessel to react and obtain a metal organic framework material;
[0007] (2) The metal organic framework material is fully mixed with ceramic powder to coat the metal organic framework material on the surface of the ceramic powder to obtain a metal organic framework coated modified composite ceramic powder.
[0008] Preferably, the metal salt is selected from one or more of aluminum nitrate, aluminum chloride, magnesium nitrate, magnesium chloride, zirconium nitrate or zirconium chloride;
[0009] Preferably, the organic ligand is selected from one or more of terephthalic acid, 2-aminoterephthalic acid, trans-1,5-cyclohexanedicarboxylic acid, trimesic acid, 1,2-cyclohexanedicarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,4-naphthalene dicarboxylic acid, 2,2'-bipyridine-4,4'-dicarboxylic acid, 2,2'-bipyridine-5,5'-dicarboxylic acid or 2,5-dihydroxyterephthalic acid;
[0010] Preferably, the solvent is selected from one or more of water, ethanol, methanol, N,N-dimethylformamide, chloroform or tetrahydrofuran;
[0011] Preferably, the ceramic powder is selected from one or more of silicon nitride, silicon carbide, zirconium oxide, lead oxide or titanium oxide.
[0012] Preferably, the mass ratio of the metal organic framework material to the ceramic powder is 1:99 to 50:50.
[0013] Preferably, the reaction temperature of step (1) is 100 to 240° C., and the reaction time is 12 to 100 hours.
[0014] Preferably, in step (2), the ceramic powder is further subjected to activation treatment before being mixed with the metal organic framework material; the specific steps of the activation treatment are: alkali washing the ceramic powder, and then filtering, washing and drying.
[0015] According to another aspect of the present invention, a composite ceramic powder prepared by a method for preparing a modified ceramic powder coated with a metal organic framework is provided.
[0016] According to another aspect of the present invention, there is provided a ceramic slurry, comprising the composite ceramic powder, a sintering aid, a resin, a photoinitiator and a dispersant.
[0017] Preferably, the sintering aid is selected from one or more of yttrium oxide, magnesium oxide or aluminum oxide;
[0018] Preferably, the resin is selected from one or more of trimethylolpropane triacrylate (TMPTA), 1,6-hexanediol diacrylate (HDDA), dipentaerythritol hexaacrylate (DPHA), ethoxylated pentaerythritol tetraacrylate (PPTTA), ethoxylated trimethylolpropane triacrylate (TMP3EOTA), isobornyl acrylate (IBOA), acryloyl morpholine (ACMO), polyethylene glycol (400) diacrylate (PEG400), and trimethylolpropane trimethacrylate (TMPTMA);
[0019] Preferably, the photoinitiator is selected from one or more of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide (TPO) and hydroxycyclohexane phenone (184);
[0020] Preferably, the dispersant is selected from one or more of polyacrylate, sodium dodecylbenzene sulfonate, polyvinyl ester, and vinyl bisstearamide.
[0021] Preferably, the mass ratio of the composite ceramic powder, sintering aid, resin, photoinitiator and dispersant is 100:5:20:1:1 to 100:50:150:30:15.
[0022] According to another aspect of the present invention, there is provided an application of the ceramic slurry, which is used for photocuring ceramic additive manufacturing.
[0023] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0024] (1) The present invention uses metal organic framework materials for coating and modification of difficult-to-curing ceramic powders, which can significantly reduce the ultraviolet absorbance of difficult-to-curing ceramic powders, increase the photocuring depth of difficult-to-curing ceramic powders, and facilitate the photocuring forming of difficult-to-curing ceramics. Finally, ceramics are prepared by photocuring forming technology. This method has the advantages of simple preparation and greatly improving the photocuring efficiency of difficult-to-form ceramics, providing a new idea for preparing difficult-to-curing ceramic powders for photocuring.
[0025] (2) The metal organic framework material of the present invention is self-assembled by metal ions and organic ligands through coordination bonds. The size and optical properties of the metal organic framework material can be adjusted by changing the type of organic ligands and adjusting the synthesis reaction temperature and reaction time. The light absorption and luminescence of the metal organic framework material can be controlled by changing the type of organic ligands and the synthesis conditions, thereby preparing a metal organic framework material with low ultraviolet absorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the ultraviolet absorption spectrum of the silicon nitride ceramic powder before and after the metal organic framework coating modification in Example 1.
[0027] Figure 2 This is a comparison chart of the single-layer curing depth of the silicon nitride ceramic slurry before and after the metal organic framework coating modification in Example 1.
[0028] Figure 3 This is the ultraviolet absorption spectrum of the silicon nitride ceramic powder before and after the metal organic framework coating modification in Example 2.
[0029] Figure 4 This is a comparison chart of the single-layer curing depth of the silicon nitride ceramic slurry before and after the metal organic framework coating modification in Example 2.
[0030] Figure 5 This is the ultraviolet absorption spectrum of the silicon carbide ceramic powder before and after the metal organic framework coating modification in Example 3.
[0031] Figure 6 This is a comparison chart of the single-layer curing depth of the silicon carbide ceramic slurry before and after the metal organic framework coating modification in Example 3. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] Example 1
[0034] Step 1: Add 22.075 g of aluminum nitrate and 4.881 g of terephthalic acid to 100 mL of deionized water, mix them by ultrasonication, put them into a reactor, and react them at 180°C for 72 hours. Cool them to room temperature, and after a series of filtering, washing, drying and other operations, obtain MOF-1 material.
[0035] Step 2: Place 100g of silicon nitride ceramic powder in 1mol / L sodium hydroxide solution for a period of time, then filter, wash and dry to obtain activated silicon nitride ceramic powder. Then add the MOF-1 material and activated silicon nitride ceramic powder prepared in the first step into ethanol, ball mill for a period of time, filter and dry to obtain MOF-1 coated modified silicon nitride ceramic powder.
[0036] Step 3: The MOF-1@silicon nitride ceramic powder prepared in the second step is fully mixed with the sintering aid yttrium oxide, the resin trimethylolpropane triacrylate (TMPTA), acryloylmorpholine (ACMO), dipentaerythritol hexaacrylate (DPHA), the photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide (TPO) and the dispersant polyacrylate, and placed in a vacuum degassing machine to finally obtain silicon nitride ceramic slurry, and the single-layer curing depth of the silicon nitride ceramic slurry is tested.
[0037] UV absorption spectra of MOF-1 before and after coating modified silicon nitride ceramic powder Figure 1 As shown. From the ultraviolet absorption spectrum, it can be seen that at a wavelength of 355nm, the ultraviolet absorbance of MOF-1 material is significantly lower than that of silicon nitride ceramic powder. The absorbance of silicon nitride ceramic powder modified by MOF-1 material coating is significantly lower than that of the original silicon nitride ceramic powder, indicating that the ultraviolet absorbance of silicon nitride ceramic powder can be significantly reduced by MOF-1 material coating. The single-layer curing depth of silicon nitride ceramic slurry before and after MOF-1 coating modification is shown in Figure 2. Figure 2 As shown. It can be seen that the single-layer curing depth of silicon nitride ceramic slurry before coating modification is 24μm, and the curing depth of MOF-1 coated modified silicon nitride ceramic slurry is 59μm. MOF-1 coating can greatly increase the single-layer curing depth of silicon nitride ceramic slurry and improve the curing performance of silicon nitride ceramic slurry. Finally, silicon nitride ceramics are formed by photocuring. Therefore, MOF-1 material can coat modified silicon nitride ceramic powder for photocuring forming.
[0038] Example 2
[0039] Step 1: Add 11 g of aluminum nitrate and 7.4 g of pyrazole dicarboxylic acid to 300 mL of deionized water, mix by ultrasonication, and react at 100°C for 24 hours. Cool to room temperature, and obtain MOF-2 material after a series of filtering, washing, drying and other operations.
[0040] Step 2: Place 100g of silicon nitride ceramic powder in 1mol / L sodium hydroxide solution for a period of time, then filter, wash and dry to obtain activated silicon nitride ceramic powder. Then add the MOF-2 material and activated silicon nitride ceramic powder prepared in the first step into ethanol, ball mill for a period of time, filter and dry to obtain MOF-2 coated modified silicon nitride ceramic powder.
[0041] Step 3: The MOF-2@silicon nitride ceramic powder prepared in the second step is fully mixed with the sintering aid yttrium oxide, resin TMPTA, 1,6-hexanediol diacrylate (HDDA), ACMO, photoinitiator TPO and dispersant sodium dodecylbenzene sulfonate, and placed in a vacuum defoamer to finally obtain silicon nitride ceramic slurry, and the single-layer curing depth of the silicon nitride ceramic slurry is tested.
[0042] UV absorption spectra of MOF-2 before and after coating modified silicon nitride ceramic powder Figure 3 As shown. From the ultraviolet absorption spectrum, it can be seen that at a wavelength of 355nm, the ultraviolet absorbance of MOF-2 material is significantly lower than that of silicon nitride ceramic powder. The absorbance of silicon nitride ceramic powder modified by MOF-2 material coating is significantly lower than that of the original silicon nitride ceramic powder, indicating that the ultraviolet absorbance of silicon nitride ceramic powder can be significantly reduced by MOF-2 material coating. The single-layer curing depth of silicon nitride ceramic slurry before and after MOF-2 coating modification is shown in Figure 4 As shown. It can be seen that the single-layer curing depth of silicon nitride ceramic slurry before coating modification is 24μm, and the curing depth of MOF-1 coated modified silicon nitride ceramic slurry is 53μm. MOF-1 coating can greatly increase the single-layer curing depth of silicon nitride ceramic slurry and improve the curing performance of silicon nitride ceramic slurry. Finally, silicon nitride ceramics are formed by photocuring. Therefore, MOF-1 material can coat modified silicon nitride ceramic powder for photocuring forming.
[0043] Example 3
[0044] Step 1: Add 22.075 g of aluminum nitrate and 4.881 g of terephthalic acid to 100 mL of deionized water, mix them by ultrasonication, put them into a reactor, and react them at 180°C for 72 hours. Cool them to room temperature, and after a series of filtering, washing, drying and other operations, obtain MOF-1 material.
[0045] Step 2: Place 100g of silicon carbide ceramic powder in 1mol / L sodium hydroxide solution for a period of time, then filter, wash and dry to obtain activated silicon carbide ceramic powder. Then add the MOF-1 material and activated silicon carbide ceramic powder prepared in the first step into ethanol, ball mill for a period of time, filter and dry to obtain MOF-1 coated modified silicon carbide ceramic powder.
[0046] Step 3: Place the MOF-1@silicon carbide ceramic powder prepared in the second step, sintering aid yttrium oxide, resin TMPTA, HDDA, ACMO, photoinitiator TPO and dispersant vinyl bisstearamide in a vacuum defoamer to obtain silicon carbide ceramic slurry and test the single-layer curing depth of the silicon carbide ceramic slurry.
[0047] UV absorption spectra of MOF-1 before and after coating modified silicon carbide ceramic powder Figure 5As shown. From the ultraviolet absorption spectrum, it can be seen that at a wavelength of 405nm, the ultraviolet absorbance of MOF-1 material is significantly lower than that of silicon carbide ceramic powder. The absorbance of silicon carbide ceramic powder modified by MOF-1 material coating is significantly lower than that of the original silicon carbide ceramic powder, indicating that the ultraviolet absorbance of silicon carbide ceramic powder can be significantly reduced by MOF-1 material coating. The single-layer solidification depth of silicon carbide ceramic slurry before and after MOF-1 coating modification is shown in Figure 6 As shown. It can be seen that the single-layer curing depth of silicon carbide ceramic slurry before coating modification is 21μm, and the curing depth of MOF-1 coated modified silicon carbide ceramic slurry is 47μm. MOF-1 coating can greatly increase the single-layer curing depth of silicon carbide ceramic slurry and improve the curing performance of silicon carbide ceramic slurry. Finally, silicon carbide ceramics are formed by photocuring. Therefore, MOF-1 material can coat modified silicon carbide ceramic powder for photocuring forming.
[0048] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing modified ceramic powder based on metal organic framework coating, characterized in that: The steps include: (1) adding a metal salt and an organic ligand into a solvent, mixing them thoroughly, and then adding them into a reaction vessel to react and obtain a metal organic framework material; (2) The metal organic framework material is fully mixed with ceramic powder to coat the metal organic framework material on the surface of the ceramic powder to obtain a metal organic framework coated modified composite ceramic powder.
2. The method for preparing a metal organic framework-coated modified ceramic powder according to claim 1, characterized in that: The metal salt is selected from one or more of aluminum nitrate, aluminum chloride, magnesium nitrate, magnesium chloride, zirconium nitrate, and zirconium chloride; The organic ligand is selected from one or more of terephthalic acid, 2-aminoterephthalic acid, trans-1,5-cyclohexanedicarboxylic acid, trimesic acid, 1,2-cyclohexanedicarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,4-naphthalene dicarboxylic acid, 2,2'-bipyridine-4,4'-dicarboxylic acid, 2,2'-bipyridine-5,5'-dicarboxylic acid, and 2,5-dihydroxyterephthalic acid; The solvent is selected from one or more of water, ethanol, methanol, N,N-dimethylformamide, chloroform, and tetrahydrofuran; The ceramic powder is selected from one or more of silicon nitride, silicon carbide, zirconium oxide, lead oxide and titanium oxide.
3. The method for preparing a metal organic framework-coated modified ceramic powder according to claim 1, characterized in that: The mass ratio of the metal organic framework material to the ceramic powder is 1:99 to 50:
50.
4. The method for preparing a metal organic framework-coated modified ceramic powder according to claim 1, characterized in that: The reaction temperature of step (1) is 100-240° C., and the reaction time is 12-100 h.
5. The method for preparing a metal organic framework-coated modified ceramic powder according to claim 1, characterized in that: In step (2), before the ceramic powder is mixed with the metal organic framework material, the ceramic powder is also subjected to activation treatment; the specific steps of the activation treatment are: alkali washing the ceramic powder, and then filtering, washing and drying.
6. Composite ceramic powder prepared according to the method for preparing modified ceramic powder coated with a metal organic framework according to any one of claims 1 to 5.
7. A ceramic slurry, characterized in that: The composite ceramic powder comprises the composite ceramic powder as claimed in claim 6, and further comprises a sintering aid, a resin, a photoinitiator and a dispersant.
8. A ceramic slurry according to claim 7, characterized in that: The sintering aid is selected from one or more of yttrium oxide, magnesium oxide, and aluminum oxide; The resin is selected from one or more of trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, dipentaerythritol hexaacrylate, ethoxylated pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, isobornyl acrylate, acryloyl morpholine, polyethylene glycol, diacrylate, and trimethylolpropane trimethacrylate; The photoinitiator is selected from one or more of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and hydroxycyclohexane phenone; The dispersant is selected from one or more of polyacrylate, sodium dodecylbenzene sulfonate, polyacrylate, and vinyl bisstearamide.
9. The ceramic slurry according to claim 7, characterized in that: The mass ratio of the composite ceramic powder, the sintering aid, the resin, the photoinitiator and the dispersant is 100:5:20:1:1 to 100:50:150:30:
15.
10. The use of a ceramic slurry according to any one of claims 7 to 9, characterized in that: Use it in photo-curing ceramic additive manufacturing.
Citation Information
Patent Citations
Porous ceramic material based on metal organic frameworks (MOFs), and preparation method thereof
CN109160824A
ZIF-8 film-coated SnO2 composite gas-sensing material and preparation method and application thereof
CN110396006A
Metal organic framework compound coated composite magnetic wave-absorbing material and preparation method thereof
CN116445131A
Photoinitiator-loaded up-conversion MOFs composite material for near-infrared light curing and preparation method of photoinitiator-loaded up-conversion MOFs composite material
CN119119328A
Flexible display panel and manufacturing method therefor
WO2020118765A1